A 12-week subchronic intramuscular toxicity study of risperidone-loaded microspheres in rats. (February 2015) - Zhang, J; Ye, L; Wang, W; Du, G; Yu, X; Zhu, X; Dong, Q; Cen, X; Guan, X; Fu, F; Tian, J
Long-acting injectable formulations of antipsychotics have been an important treatment option to increase the compliance of the patient with schizophrenia by monitoring drug administration and identifying medication noncompliance and to improve the long-term management of schizophrenia. Risperidone, a serotoninergic 5-HT2 and dopaminergic D2 receptor antagonist, was developed to be a long-acting sustained-release formulation for the treatment of schizophrenia. In this study, 12-week subchronic toxicity study of risperidone-loaded microspheres (RMs) in rats by intramuscular injection with an 8-week recovery phase was carried out to investigate the potential subchronic toxicity of a novel long-acting sustained-release formulation. The results indicated that the dosage of 10–90 mg/kg of RM for 2 weeks did not cause treatment-related mortality. The main drug-related findings were contributed to the dopamine D2 receptor and α1 -adrenoceptor antagonism of risperidone such as elevation of serum and pituitary prolactin levels and ptosis and changes in reproductive system (uterus, ovary, vagina, mammary gland, testis, seminal vesicle, epididymis, and prostate). In addition, foreign body granuloma in muscle at injection sites caused by poly-lactide-co-glycolide was observed. At the end of the recovery phase, these changes mostly returned to normal. The results indicated that RM had a good safety profile in rats.